P175 Bipolar endoscopic radiofrequency ablation for the management of occluded metal stents due to tumour ingrowth. (19th June 2022) - Awadelkarim, Bidour; Long, Matthew; Wong, Terry; Geraghty, Joe; Oppong, Kofi; Nayar, Manu; Leeds, John
Abstract : Introduction: Malignant biliary obstruction is treated using metal stents but some patients can develop stent dysfunction. Radiofrequency ablation (RFA) causes coagulative necrosis of tissue which can be used to ablate ingrowth of tumour in previously placed stents. There are no comparative studies examining whether RFA has an effect on adverse event rates, stent patency, reintervention rate or survival. We report a multicentre experience in the use of RFA for treating occluded stents due to tumour ingrowth. Methods: Retrospective analysis of patients with a confirmed diagnosis of cancer and blocked stent treated with RFA were included from 3 UK centres. Standard protocol was 10 W at 75 degrees for 2 minutes under fluoroscopic guidance. For strictures longer than 20mm overlapping ablation was given. Age, sex, cancer type and stage, date of intervention, adverse events, reinterventions, oncological treatments and date of death or last follow up were recorded. Controls were age, sex and disease type/stage matched patients receiving biliary stenting without RFA for occluded stents. Kaplan-Meier survival analysis was performed with Cox proportional hazards regression to identify independent factors associated with survival and need for reintervention. Results: 57 patients (mean age 69.2 years, 41 males) were included in the study, of which, 28 received RFA and 29 were controls. There were no significant differences in age, sex distribution, tumour type, tumour stage or rates of chemotherapy before or after stent occlusion. There was one adverse event in the control group (bile duct perforation) but no occurrences of cholangitis, pancreatitis, bleeding or cholecystitis in either group. There was no significant difference in reintervention rate (16/28 for RFA vs. 14/29 for controls, p=0.599) or time to reintervention (74 days for RFA vs 83 days for controls, p=0.512) between the two groups. There was no difference in the unadjusted overall survival between the two groups (HR 0.696, 0.39 – 1.25, p=0.219) but Cox regression showed improved survival in those receiving chemotherapy following intervention (HR 0.50, 0.26 – 0.95, p=0.0347) and those receiving RFA (HR 0.56, 0.29 – 1.02, p=0.058). Adjusting the survival curves for receipt of chemotherapy showed significant survival advantage for patients receiving RFA and chemotherapy (HR 0.36, 0.13 – 0.96, p=0.047). Conclusions: RFA is a safe adjunct in the management of occluded biliary metal stents due to tumour ingrowth. There appears to be survival benefit but only in those that receive chemotherapy following RFA. Larger, prospective, randomised studies including quality of life assessments are needed.